(untitled) (Revista Latino-Americana de Enfermagem, 2011)
With the aim of describing barriers to screening for prostate cancer, a domicile survey was carried out covering 160 men of a Family Health Strategy (FHS) area. Slightly over half had undergone the examination. Regarding beliefs related to the disease, 95% of the men believed there is a cure if detected early, 29.4% mentioned the possibility of a normal life while ill, 56.3% believed it may be asymptomatic, 36.1% agreed/disagreed that the treatment is worse than the disease and 34.4% agreed that the examination affects masculinity and that if you are well it is not necessary to perform it. Regarding barriers, 15% reported that the physician had never requested it, 10.9% did not consider it important and 16.9% were afraid to take the examination. While not the sole determinant, the dissemination of adequate knowledge regarding the examination can constitute a key strategy for the formation of a positive attitude in relation to early detection.